Life cycle assessment of various cropping systems utilized for producing biofuels: Bioethanol and biodiesel - Kim, S.; Dale, B.E.
A life cycle assessment of different cropping systems emphasizing corn and soybean production was performed, assuming that biomass from the cropping systems is utilized for producing biofuels (i.e., ethanol and biodiesel). The functional unit is defined as 1 ha of arable land producing biomass for biofuels to compare the environmental performance of the different cropping systems. The external functions are allocated by introducing alternative product systems (the system expansion allocation approach). Nonrenewable energy consumption, global warming impact, acidification and eutrophication are considered as potential environmental impacts and estimated by characterization factors given by the United States Environmental Protection Agency (EPA-TRACI). The benefits of corn stover removal are (1)lower nitrogen related environmental burdens from the soil, (2)higher ethanol production rate per unit arable land, and (3)energy recovery from lignin-rich fermentation residues, while the disadvantages of corn stover removal are a lower accumulation rate of soil organic carbon and higher fuel consumption in harvesting corn stover. Planting winter cover crops can compensate for some disadvantages (i.e., soil organic carbon levels and soil erosion)of removing corn stover. Cover crops also permit more corn stover to be harvested. Thus, utilization of corn stover and winter cover crops can improve the eco-efficiency of the cropping systems. When biomass from the cropping systems is utilized for biofuel production, all the cropping systems studied here offer environmental benefits in terms of nonrenewable energy consumption and global warming impact. Therefore utilizing biomass for biofuels would save nonrenewable energy, and reduce greenhouse gases. However, unless additional measures such as planting cover crops were taken, utilization of biomass for biofuels would also tend to increase acidification and eutrophication, primarily because large nitrogen (and phosphorus)-related environmental burdens are released from the soil during cultivation.
Keywords: BD20 FUEL; BIODIESEL; BIOFUEL; CORN GRAIN; CORN-SOYBEAN ROTATION; CORN STOVER; CROPPING SYSTEM; E10 FUEL; ECO-EFFICIENCY; ETHANOL; LIFE CYCLE ASSESSMENT; SYSTEM EXPANSION ALLOCATION; WINTER COVER CROP